The role of kinship in bi-national couples: Intergenerational solidarity in Turkish-German families - Tecklenburg, Rena; Boehnke, Mandy (Frontiers in Sociology, 2022)
Intermarriages, i.e. marriages between people from different ethnic backgrounds, have increased in recent years in many parts of the world and also in Germany (Baykara-Krumme 2020). These marriages, often between an immigrant and a native partner, have various implications for family dynamics. Previous studies have shown that marriage or cohabitation with a partner who has a different cultural and religious background can be more conflictual (Hohmann-Marriott and Amato 2008) and has a higher risk of divorce (Milewski and Kulu 2014). In addition, intermarriages also experience less support from relatives and family members (Kalmijn et al. 2005), which may be due to proximity but also lack of acceptance or sanctions (Kalmijn 1998). To date, research has focused on the causes of ethnic exogamy, partnership quality, and fertility among interethnic couples. Using problem-centered interviews (Witzel and Reiter 2012) with Turkish-German couples living in Germany, the present study aims to broaden this perspective by looking at kin relationships (modes of interaction, spatial and emotional closeness, assistance and support, agreement on values and responsibilities), which have hardly been studied in bi-national families so far. The study pursues a qualitative research design that allows tracing kinship relations and perceived negotiation processes. We are interested in the specific conditions of bi-national families (married couples with children) and their interactions with the respective family networks. Using the intergenerational solidarity typology (Bengtson and Roberts 1991) as an heuristic for the qualitative content analysis (Kuckartz 2014, Schreier 2012) the results will provide answers to the question what role kinship networks play in these partnerships and how their possibly different demands are balanced. The analysis of the interviews shows that in most cases the quality of relationships is high in both Turkish and German kinship networks and is characterized by openness and cordiality. As a result, relatives from both sides offer emotional, financial, or childcare support to the interviewed families, but differ in the type of support mainly due to physical proximity. Based on the results, we cannot claim that family cohesion is generally closer on one side of the extended family.